Identification of stable reference genes in Edwardsiella ictaluri for accurate gene expression analysis - Jingjun Lu; Hossam Abdelhamed; Nawar Al-Janabi; Nour Eissa; Mark Lawrence; Attila Karsi (PLoS ONE, 2025)
Edwardsiella ictaluri is a Gram-negative bacterium causing enteric septicemia of catfish (ESC), leading to significant economic losses in the catfish farming industry. RT-PCR analysis is a powerful technique for quantifying gene expression, but normalization of expression data is critical to control experimental errors. Using stable reference genes, also known as housekeeping genes, is a common strategy for normalization, yet reference gene selection often lacks proper validation. In this work, our goal was to determine the most stable reference genes in E. ictaluri during catfish serum exposure and various growth phases. To this goal, we evaluated the expression of 27 classical reference genes (16S rRNA, abcZ, adk, arc, aroE, aspA, atpA, cyaA, dnaG, fumC, g6pd, gdhA, glnA, gltA, glyA, grpE, gyrB, mdh, mutS, pgi, pgm, pntA, recA, recP, rpoS, tkt, and tpi) using five analytical programs (GeNorm, BestKeeper, NormFinder, Comparative ΔCT, and Comprehensive Ranking). Results showed that aspA, atpA, dnaG, glyA, gyrB, mutS, recP, rpoS, tkt, and tpi were the most stable reference genes during serum exposure, whereas fumC, g6pd, gdhA, glnA, and mdh were the least stable. During various growth phases, aspA, g6pd, glyA, gyrB, mdh, mutS, pgm, recA, recP, and tkt were the most stable, while 16S rRNA, atpA, grpE, and tpi were the least stable. At least four analysis methods confirmed the stability of aspA, glyA, gyrB, mutS, recP, and tkt during serum exposure and different growth stages. However, no consensus was found among the programs for unstable reference genes under both conditions.